Contributions to students with blindness from an educational program on introduction to the tactile cartographic language - Fabiana Cristina Giehl; Juliane Aparecida Campos (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
This text analyzes the contributions of an Educational Program for the Introduction to Cartographic Tactile Language for students with blindness. Therefore, it took action research, outlined by case study, developed with qualitative approach. Participants in this study were two teachers of specialized educational service area (ESA), two teachers of ordinary school and two students with blindness with different ages (seven and ten years). The program in question contributed to the improvement of the capacity of the participating students to identify the tactile cartographic variables used on maps, so to be able to read them. Thus, it is suggested that the Tactile Cartography is present in the curricular matrices of the Geography teacher training courses, Pedagogy and other degrees or training proposals that somehow are directed to the preparation of teachers for performance with students with blindness.